Role of maternal–fetal immune tolerance in the establishment and maintenance of pregnancy - Jingjing Wang; Tao Han; Xiaoming Zhu; Yanjie Yin (Chinese Medical Journal, 2024)
Abstract. Normal pregnancy is a contradictory and complicated physiological process. Although the fetus carries the human leukocyte antigen (HLA) inherited from the paternal line, it does not cause maternal immune rejection. As the only exception to immunological principles, maternal–fetal immune tolerance has been a reproductive immunology focus. In early pregnancy, fetal extravillous trophoblast cells (EVTs) invade decidual tissues and come into direct contact with maternal decidual immune cells (DICs) and decidual stromal cells (DSCs) to establish a sophisticated maternal–fetal crosstalk. This study reviews previous research results and focuses on the establishment and maintenance mechanism of maternal–fetal tolerance based on maternal–fetal crosstalk. Insights into maternal–fetal tolerance will not only improve understanding of normal pregnancy but will also contribute to novel therapeutic strategies for recurrent spontaneous abortion, pre-eclampsia, and premature birth.